2005
DOI: 10.1207/s15548430jlr3702_5
|View full text |Cite
|
Sign up to set email alerts
|

Third through Sixth Graders' Perceptions of High-Stakes Testing

Abstract: The purpose of this study was to explore elementary students' perceptions of high-stakes testing. Although researchers have investigated the perceptions of teachers (Barksdale-Ladd & Thomas, 2000;Gordon & Reese, 1997;Hoffman, Assaf, & Paris, 2001), parents (Barksdale-Ladd & Thomas, 2000), administrators (Nolen, Haladyna, & Haas, 1999), student teachers (Sturtevant, White, & Dunlap, 2001), and even policy makers (Atkinson & Miller, 1999), little is known about children's perceptions of high-stakes testing. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
60
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(62 citation statements)
references
References 16 publications
(30 reference statements)
2
60
0
Order By: Relevance
“…Studies emerging from the US in the context of NCLB have tended to focus more on state mandatory tests and their impact on teachers, students, school districts and school or state accountability. With this dramatic expansion of large-scale testing emerged a recognition by some scholars that the voices being heard regarding the intended and unintended consequences of these tests were predominately adult (teachers, parents, education managers, test developers) and that fewer studies investigated students' opinions directly (Triplett and Barskdale, 2005;Weiss, 2009). …”
Section: Student Perspectives On High-stakes Testsmentioning
confidence: 99%
“…Studies emerging from the US in the context of NCLB have tended to focus more on state mandatory tests and their impact on teachers, students, school districts and school or state accountability. With this dramatic expansion of large-scale testing emerged a recognition by some scholars that the voices being heard regarding the intended and unintended consequences of these tests were predominately adult (teachers, parents, education managers, test developers) and that fewer studies investigated students' opinions directly (Triplett and Barskdale, 2005;Weiss, 2009). …”
Section: Student Perspectives On High-stakes Testsmentioning
confidence: 99%
“…Two US studies used student drawings to analyse their perceptions of high stakes testing (Wheelock, Bebell and Haney 2000;Triplett and Barksdale 2005). They found that the depictions generally reflected anxiety, anger, boredom and withdrawal, with disaffection greater among older students.…”
Section: The Unintended Consequences Of High Stakes Testingmentioning
confidence: 99%
“…Other researchers have likewise documented the need teachers feel to teach to the test (Herman & Golan, 1993;Hillocks Jr. & Wallace, 2002). Additional negative effects cited in the literature include cheating (e.g., teachers giving hints, changing answers) (AmreinBeardsley, Berliner, & Rideau, 2010;Hoffman, Assaf, & Paris, 2001;Nichols & Berliner, 2007;Wilson, Bowers, & Hyde, 2011), emotional stress (Hargrove et al, 2000;Herman & Golan, 1993;Sheldon & Biddle, 1998;Smith, 1991;Smith & Rottenberg, 1991;Triplett & Barksdale, 2005), and the use of educational triage practices (Booher-Jennings, 2005;Neal & Schanzenbach, 2010;Reback, 2008) in which teachers focused on near passing students while providing less instructional time with the lowest performing students.…”
Section: Unintended Consequences Of High-stakes Testingmentioning
confidence: 99%